The floating feldmans ebook - Friedland, Elyssa (2019)
A family vacation dredges up a boatload of trouble in the next witty, insightful novel from the acclaimed author of The Intermission . "An irresistible drama filled with humor and heart-tugging emotion about family and what it means to belong. I absolutely adore Friedland's warm, witty writing!"—Emily Giffin, #1 New York Times bestselling author of All We Ever Wanted Sink or swim. Or at least that's what Annette Feldman tells herself when she books a cruise for her entire family. It's been over a decade since the Feldman clan has spent more than twenty-four hours under the same roof, but Annette is determined to celebrate her seventieth birthday the right way. Just this once, they are going to behave like an actual family. Too bad her kids didn't get the memo. Between the troublesome family secrets, old sibling rivalries, and her two teenage grandkids, Annette's birthday vacation is looking more and more like the perfect storm. Adrift together on the open seas, the Feldmans will each face the truths they've been ignoring—and learn that the people they once thought most likely to sink them are actually the ones who help them stay afloat.